1997
DOI: 10.1007/s004120050218
|View full text |Cite
|
Sign up to set email alerts
|

Xist RNA is associated with the transcriptionally inactive XY body in mammalian male meiosis

Abstract: In eutherian mammals, X inactive-specific transcripts (Xist) are expressed in somatic cells possessing more than one X chromosome, and in germline cells of males, in which the single X chromosome is transcriptionally inactive. In early meiosis of males the sex chromosomes form an inactive XY nuclear compartment (XY body). We show by in situ reverse-transcribed polymerase chain reaction that Xist RNA is concentrated in the XY body. This fine localization suggests that Xist RNA is involved in inactivation of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
44
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(44 citation statements)
references
References 52 publications
0
44
0
Order By: Relevance
“…The list includes: XY40 (Smith and Benavente 1992;Alsheimer et al 1997), BRCA1 (Scully et al 1997), ATR (Keegan et al 1996), XMR (Escalier and Garchon 2000), and also Xist RNA, a nontranslated RNA involved in the inactivation of the X chromosomes in female somatic cells and X and Y chromosomes in male meiotic cells (Ayoub et al 1997). While the function of many of these proteins remains uncertain, recent works have yielded important clues as regards the roles of BRCA1 and ATR.…”
Section: Brca1 and Atr Associate Specifically To Unsynapsed Sex Chrommentioning
confidence: 99%
“…The list includes: XY40 (Smith and Benavente 1992;Alsheimer et al 1997), BRCA1 (Scully et al 1997), ATR (Keegan et al 1996), XMR (Escalier and Garchon 2000), and also Xist RNA, a nontranslated RNA involved in the inactivation of the X chromosomes in female somatic cells and X and Y chromosomes in male meiotic cells (Ayoub et al 1997). While the function of many of these proteins remains uncertain, recent works have yielded important clues as regards the roles of BRCA1 and ATR.…”
Section: Brca1 and Atr Associate Specifically To Unsynapsed Sex Chrommentioning
confidence: 99%
“…Previous studies demonstrated that several genes on the X chromosome are subject to transcriptional repression during meiosis, beginning at pachytene with reactivation by the spermatid stage (8,9). Furthermore, RNA polymerase II has been shown to be excluded from the XY body at pachytene (10,11). However, the mechanism and even the extent of X and Y inactivation (XYi) during spermatogenesis are not known.…”
mentioning
confidence: 99%
“…The effect of the hemizygous state on Xist expression was arguably small (twofold). However, because Xist normally is expressed only at very low levels in the male germ line (several RNA copies only) (18,19), the small decrease was likely all that could be observed in the germ line. Xist is not fully up-regulated until the gene is passed on to female progeny.…”
Section: Resultsmentioning
confidence: 99%
“…During imprinted XCI, Xist is expressed for the first time from the X p at the time of zygotic gene activation in the two-cell embryo (16,17). In the paternal germ line, however, Xist RNA is expressed only at low levels, suggesting that it is not required for spermatogenesis (18,19). Consistent with this notion, male mice with an Xist deletion are fertile (12,20).…”
mentioning
confidence: 84%